Molecular phylogeny of Annonaceae species from Binh Chau-Phuoc Buu Nature Reserve based on two chloroplast gene regions - Nguyen, Ngoc Duyen; Luu, Thao Nguyen; Trinh, Ngoc Nam; Le, Van Son; Van, Hong Thien (Journal of Phytology, 2022)
In this study, based on molecular biology techniques, the matK and trnL-F regions of ten Annonaceae species grown in Binh Chau-Phuoc Buu Nature Reserve, Vietnam were successfully amplified and sequenced for the first time. Along with other highly homologous DNA sequences from the GenBank database, the molecular phylogeny of ten studied species was also established. By using the alignment tool of NCBI database, the percentage of identity among sequences of studied species was also presented. The study aims to partially contribute to the further understanding of the evolutionary relationships among Annonaceae species.